Podobieństwo semantyczne w analizie danych przekrojowych - Lula, Paweł; Paliwoda-Pękosz, Grażyna (Semantic Relatedness in Spatial Data Analysis, 2009)
The main objective of this paper was to compare semantic distance and semantic similarity measures for ontology-based data. First, the advantages of an ontology-based object description were discussed. Subsequently, similarity measures and distance measures that are based on the ontology hierarchical structure and relationships between objects were presented. Second, examples of measures for European Union countries were counted and then compared, taking into account their theoretical background, computational aspects and possibilities of interpretations and applications. Finally, directions for further research were outlined. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 104-112